A Comparative Study on Delivery of Externally Attached DNA by Papillomavirus VLPs and Pseudoviruses - Sarah Brendle; Nancy Cladel; Karla Balogh; Samina Alam; Neil Christensen; Craig Meyers; Jiafen Hu (Vaccines, 2021)
Human papillomavirus (HPV) 16 capsids have been chosen as a DNA delivery vehicle in many studies. Our preliminary studies suggest that HPV58 capsids could be better vehicles than HPV16 capsids to deliver encapsidated DNA in vitro and in vivo. In the current study, we compared HPV16, HPV58, and the cottontail rabbit papillomavirus (CRPV) capsids either as L1/L2 VLPs or pseudoviruses (PSVs) to deliver externally attached GFP-expressing DNA. Both rabbit and human cells were used to test whether there was a species-specific effect. DNA delivery efficiency was determined by quantifying either GFP-expressing cell populations or mean fluorescent intensities (MFI) by flow cytometry. Interestingly, CRPV and 58-VLPs and PSVs were significantly more efficient at delivering attached DNA when compared to 16-VLPs and PSVs. A capsid/DNA ratio of 2:1 showed the highest efficiency for delivering external DNA. The PSVs with papillomavirus DNA genomes also showed higher efficiency than those with irrelevant plasmid DNA. HPV16L1/58L2 hybrid VLPs displayed increased efficiency compared to HPV58L1/16L2 VLPs, suggesting that L2 may play a critical role in the delivery of attached DNA. Additionally, we demonstrated that VLPs increased in vivo infectivity of CRPV DNA in rabbits. We conclude that choosing CRPV or 58 capsids to deliver external DNA could improve DNA uptake in in vitro and in vivo models.